2011
DOI: 10.3329/jhpn.v29i2.7857
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin D Deficiency among Adult Population of Isfahan City, Iran

Abstract: Determination of vitamin D status in different age-groups in a community and in different climates of a country is necessary and has important implications for general health. The study was conducted to determine the prevalence of vitamin D deficiency among the adult population of Isfahan, a centrally-located city in Iran. In this cross-sectional study, 1,111 healthy people—243 men and 868 women—aged 41.4 (mean 14 and range 20-80) years, who attended a single-consultation outpatient clinic, were selected. Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
145
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(167 citation statements)
references
References 29 publications
17
145
1
4
Order By: Relevance
“…Studies from other geographic regions of Iran have also shown high proportion of vitamin D deficiency in women and lower serum 25-OHD in young and middle aged females compared with older women [3,10,30]. Similar observations have been reported from other countries [31,32].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Studies from other geographic regions of Iran have also shown high proportion of vitamin D deficiency in women and lower serum 25-OHD in young and middle aged females compared with older women [3,10,30]. Similar observations have been reported from other countries [31,32].…”
Section: Discussionsupporting
confidence: 77%
“…Several factors including low intake of vitamin D, inadequate sunlight exposure, clothing were shown to be associated factors of low vitamin D in women [3,10,30,34].…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher prevalence of vitamin D insufficiency in women in Gaza City than in Hebron supports this hypothesis since exposure to sunlight is less common in the former. A high prevalence of vitamin D insufficiency in women has been described in other Middle Eastern countries (21)(22)(23)(24) . The results of the study suggest that the content of vitamin D in the wheat flour may need to be increased.…”
Section: Discussionmentioning
confidence: 99%
“…19 In another study in Isfahan, this rate was reported to be about 50.8%. 20 Another study in the United States investigated 62 RA patients in terms of vitamin D and DAS28 levels and showed that about 61% of patients had low vitamin D levels (less than 30 ng/mL). An inverse relationship was also found between vitamin D level and high disease activity (DAS28 >2.6), while the relationship between the vitamin D level and controlled disease (DAS28 <2.6) was not significant.…”
Section: Discussionmentioning
confidence: 99%